2020
DOI: 10.1186/s13568-020-01096-2
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis, characterization of PLGA coated folate-mediated multiple drug loaded copper oxide (CuO) nanoparticles and it’s cytotoxicity on nasopharyngeal cancer cell lines

Abstract: Cytotoxicity of CuO nanoparticles (NPs) are an impediment in utilizing them as an effective nanocarriers of chemotherapeutic drugs for targeted drug delivery in nasopharyngeal cancer. In our current study, we have designed a two-step synthesis and coating of CuO NPs with different concentrations of PLGA (polylactide-co-glycolide) to reduce the cytotoxicity. This was further conjugated with folic acid to enhance targeting to specific tissue. The multiple drugs loaded in the NPs were two potent anticancer drugs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…This may be due to the presence of residual free carboxylic acid groups (−COO -) of FA. Similar findings were previously mentioned for shifting the negative values of the zeta potential toward the positive one for different nanoparticles after FA conjugation [15,[69][70][71].…”
Section: Discussionsupporting
confidence: 88%
“…This may be due to the presence of residual free carboxylic acid groups (−COO -) of FA. Similar findings were previously mentioned for shifting the negative values of the zeta potential toward the positive one for different nanoparticles after FA conjugation [15,[69][70][71].…”
Section: Discussionsupporting
confidence: 88%
“…The broad band around the 3200-3800 cm -1 region indicates the formation of hydrogen bonding between the top phase components 47,79,85,86 . The peak of the carbonyl group of DOX appears at 1730 cm -1 , while the peaks standing for the OH of primary amine and NH appear at 3330 and 3540 cm -1 , respectively [87][88][89][90] . Although DOX peaks were overlapped with the signals of PEG and lysine in DOX@nanoformulation spectrum, DOX molecules can be incorporated into the complexes formed by hydrogen bonding due to the presence of phenolic, amino and hydroxyl groups in its structure, which can form hydrogen bonding, and lead to the formation of a drug-loaded nanoformulation 69,70 .…”
Section: Ftir Analysismentioning
confidence: 99%
“…Although the antibacterial mechanism of copper has not been fully understood, recently, this ion has been widely used due to its usage in nanoparticle fabrication. Many studies have identified the anticancer properties of CuO nanoparticles [21]. CuO nanoparticles disrupt the cellular communication network by perturbation of cell signaling pathways.…”
Section: Caspase Measurementmentioning
confidence: 99%